Reklama poradników w prasie wileńskiej w II połowie XVIII w. - Jakubėnas, Regina (Slavistica Vilnensis, 2009)
In late eighteenth century several guidebooks were advertised in Vilnius periodicals. At that time guidebooks constituted one of the most popular kinds of reading literature and included agricultural, farming, medical, herbal and spiritual guides. Some of the publications were to provide entertainment and amuse readers; however, there were authors who tried to point out the causes of some frequent diseases and urged readers to take greater care of their hygiene and health. Advertisements of this kind in the Lithuanian press may serve as evidence of their popularity not only in Europe, but in the Grand Duchy of Lithuania as well.